Effects of dietary γ‐aminobutyric acid supplementation on antioxidant status, blood hormones and meat quality in growing‐finishing pigs undergoing transport stress. Issue 2 (22nd December 2019) - Bi, Chongpeng; Yin, Jiajia; Yang, Wei; Shi, Baoming; Shan, Anshan
Abstract: γ‐Aminobutyric acid (GABA) is a natural nonprotein amino acid distributed in animals, plants and microbes. GABA is an inhibiting neurotransmitter which takes great effect in mammalian central nervous system. We carried out the research to study the influence of GABA on blood hormone concentrations, antioxidant status and meat quality in fattening pigs after transportation. The 72 pigs with a starting weight of approximately 32.67 ± 0.62 kg were randomly allocated to 2 groups based on dietary treatments, containing 6 replicates with 6 pigs in each. The pigs were fed dietary supplementation of GABA (0 or 30 mg/kg of diets) for 74 days. Twelve pigs were randomly selected from each group and assigned to the either 1 hr of transport (T group) or no transport (N group), resulting in two‐factor factorial design. Compared to the control, GABA supplementation increased average daily gain (ADG) ( p  < .01) and decreased feed–gain ratio (F/G) ( p  < .05). The pH45 min was lower and drip loss was greater in the longissimus muscles (LM) of post‐slaughter of transported pigs ( p  < .05). The pH45 min of 0/T group (group with 0 mg/kg GABA and transport) was significantly lower than the pH45 min of the 30/T group (diet × transport; p  < .05). GABA supplementation significantly increased serum glutathione peroxidase (GSH‐Px) concentration ( p  < .05) before transportation. Following transport, pigs fed GABA had decreased concentrations of serum malonaldehyde (MDA), adrenal cortical hormone and cortisol ( p  < .05). The results indicate that feeding GABA significantly increased the growth performance of growing‐finishing pigs. The transportation model negatively impacted meat quality, antioxidant indexes and hormone parameters, but dietary supplementation of GABA could suppress the rise of drip loss of LM, ACTH and COR and suppress the drop of pH45 min of LM after transportation stress in growing‐finishing pigs. Feeding GABA alleviated transportation stress in pigs.